1978
DOI: 10.1128/iai.19.2.562-569.1978
|View full text |Cite
|
Sign up to set email alerts
|

Protein-free and low-protein media for the cultivation of Leptospira

Abstract: A protein-free medium composed of charcoal-detoxified Tweens (polysorbates), vitamins B12 and B1, inorganic salts, and an organic buffer is described that supports the growth and subculture of pathogenic and saprophytic Leptospira.Growth was initiated from small inocula, and cell densities of 109 organisms per

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Leptospira interrogans serovar pomona H10-414 was maintained at 30°C in bovine serum albumin-Tween 80 medium (8). Virulence was maintained by hamster back passage as previously described (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leptospira interrogans serovar pomona H10-414 was maintained at 30°C in bovine serum albumin-Tween 80 medium (8). Virulence was maintained by hamster back passage as previously described (7).…”
mentioning
confidence: 99%
“…Virulence was maintained by hamster back passage as previously described (7). One volume of inoculum culture was added to 200 volumes of protein-free culture medium prepared as previously described (8), allowed to stand at 30°C for 3 days, and then aerated on a gyratory shaker at 30°C for 3 to 4 days. Final cell densities of 8 x 108 to 9 x 108 leptospires per ml were obtained.…”
mentioning
confidence: 99%
“…In this study, leptospira was cultivated in PFM supplemented with 0.1% bovine serum albumin. It was reported that immunogenicity of leptospires cultivated in PFM was similar to those prepared in serum-containing media (8,9). Reduction of any serum or albumin concentration in medium is an effective means for avoiding the adverse reaction of vaccine in the immunized host.…”
Section: Discussionmentioning
confidence: 86%
“…TM antigen. Leptospira interrogans serovar canicola strain Hond Utrecht-IV was grown in Bey and Johnson's protein-free medium (5) at 30 C for 1 week. Serovar specific TM antigen was extracted and purified from the organisms as previously described (16).…”
Section: Methodsmentioning
confidence: 99%